Correction: Qualitative and quantitative analysis of fatty acid profiles of Chinese pecans (Carya cathayensis) during storage using an electronic nose combined with chemometric methods. Issue 77 (17th October 2017) - Jiang, Shui; Wang, Jun; Sun, Yubing
Abstract : Correction for 'Qualitative and quantitative analysis of fatty acid profiles of Chinese pecans ( Carya cathayensis ) during storage using an electronic nose combined with chemometric methods' by Shui Jiang et al., RSC Adv., 2017, 7, 46461–46471.